2016
DOI: 10.1016/j.chb.2015.07.067
|View full text |Cite
|
Sign up to set email alerts
|

Watch what I do, not what I say I do: Computer-based avatars to assess behavioral inhibition, a vulnerability factor for anxiety disorders

Abstract: Behavioral inhibition (BI), a tendency to withdraw from or avoid novel social and non-social situations, is a personality trait which can confer risk for anxiety disorders. Like many personality traits, BI is often assessed via self-report questionnaires where respondents rate themselves for frequency of certain behaviors or feelings. However, questionnaires have inherent limitations, particularly in psychiatric populations where there may be unawareness of deficit. A viable alternative may be virtual environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
44
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(57 citation statements)
references
References 52 publications
12
44
1
Order By: Relevance
“…The study also replicated prior findings (Myers et al, 2016) that task performance predicts participants’ self-reported tendency to engage in avoidant behavior, assessed by AMBI. The prior study examined a sample that was younger, more educated, and highly computer literate.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The study also replicated prior findings (Myers et al, 2016) that task performance predicts participants’ self-reported tendency to engage in avoidant behavior, assessed by AMBI. The prior study examined a sample that was younger, more educated, and highly computer literate.…”
Section: Discussionsupporting
confidence: 85%
“…Although our prior article (Myers et al, 2016) found a strong correlation between task and AMBI scores (r=.783, r 2 =.613), we did not have preliminary data regarding correlations with PCL scores. Accordingly, we based power calculations on the sample size needed to detect a medium effect size (r=.3, r 2 =.09) at 80% power, if such an effect exists.…”
Section: Methodscontrasting
confidence: 65%
See 3 more Smart Citations